Prevalence and treatment outcomes of hydrocephalus among children with craniofacial syndromes - Saga Jönsson; Daniel Nilsson; Peter Tarnow; Giovanni Maltese; Madiha Bhatti-Søfteland; Lars Kölby; Tobias Hallén (Journal of Plastic Surgery and Hand Surgery)
Introduction: Hydrocephalus is more common in patients with craniofacial syndromes (CS) relative to non-syndromic craniosynostosis, and the optimal management is challenging. This study examined the prevalence and treatment outcomes of hydrocephalus among children with CS.